THE USE OF ENVIRONMENTALLY FRIENDLY LEARNING MEDIA IN FOSTERING STUDENTS' ENVIRONMENTAL CARE ATTITUDES IN THE DIGITAL ERA AT ISLAMIC ELEMANTARY SCHOOL AT-TAQWA BONDOWOSO - Karyodiputro, Muhammad Ikrom (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
This research is motivated by the attention of educational institutions (Islamic Elememtary School At-Taqwa Bondowoso) to the preservation of the natural environment amid the widespread impact of technological development in the digital era. The objectives of this research are: 1) Knowing the use of environmentally friendly learning media in growing students' environmental care attitudes in the digital era at Islamic Elememtary School At-Taqwa Bondowoso. 2) Knowing the results of the use of environmentally friendly learning media on the growth of students' environmental care attitudes at Islamic Elememtary School At-Taqwa Bondowoso. The method used in this research is a qualitative approach with the type of field research and using data collection techniques of observation, interview and documentation. Data analysis is done through data reduction, data display, and conclusion drawing in the form of verification. The results of this study are the use of environmentally friendly learning media in fostering students' environmental care attitudes in the digital era at Islamic Elememtary School At-Taqwa Bondowoso is through the use of used goods in the surrounding environment by actively involving students in developing their creativity in processing used goods into learning aids.